2021
DOI: 10.4314/sajas.v51i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil and apple pomace affect fermentation and aerobic stability of alfalfa silage

Abstract: This study assessed the effects of the additions of an essential oil (EO), composed of ricinoleic acid, cardol, cardanol, and apple pomace, on fermentation quality and aerobic stability of alfalfa silages. The experimental treatments consisted of T1) alfalfa (control), T2) alfalfa with EO, T3) alfalfa (75%) with apple pomace (25%), T4) alfalfa (75%) with apple pomace (25%) and EO, T5) alfalfa (50%) with apple pomace (50%), T6) alfalfa (50%) with apple pomace (50%) and EO, T7) alfalfa (25%) with apple pomace (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…x FOR PEER REVIEW 3 of 14 branched-chain volatile fatty acids (BCVFA), ratio acetate to propionate (C2:C3), dry matter digestibility (DMD), and organic matter digestibility (OMD). [20] 2018 Alfalfa Cumin 300-500 Akinci and Onenc [21] 2021 Vetch-oat Cumin 200-500 Junior et al [22] 2019 Sugarcane Lemongrass 1000-3000 Duru [23] 2020 Alfalfa Lavender flower 5-20 Soycan-Onec et al [24] 2015 Field pea Origanum, Cinnamon, Mix (Origanum and Cinnamon) 400 Li et al [25] 2022 Mulberry Amomum villosum 5 Besharati et al [26] 2022 Alfalfa and apple pulp Mix (ricinoleic acid, cardol, cardanol) 500 Vaičiulien ė et al [27] 2022 Perennial ryegrass, Red clover, and Blue alfalfa Oregano and Thymol 20…”
Section: Database Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…x FOR PEER REVIEW 3 of 14 branched-chain volatile fatty acids (BCVFA), ratio acetate to propionate (C2:C3), dry matter digestibility (DMD), and organic matter digestibility (OMD). [20] 2018 Alfalfa Cumin 300-500 Akinci and Onenc [21] 2021 Vetch-oat Cumin 200-500 Junior et al [22] 2019 Sugarcane Lemongrass 1000-3000 Duru [23] 2020 Alfalfa Lavender flower 5-20 Soycan-Onec et al [24] 2015 Field pea Origanum, Cinnamon, Mix (Origanum and Cinnamon) 400 Li et al [25] 2022 Mulberry Amomum villosum 5 Besharati et al [26] 2022 Alfalfa and apple pulp Mix (ricinoleic acid, cardol, cardanol) 500 Vaičiulien ė et al [27] 2022 Perennial ryegrass, Red clover, and Blue alfalfa Oregano and Thymol 20…”
Section: Database Developmentmentioning
confidence: 99%
“…However, some investigations revealed that EO supplementation reduced total VFA, dry matter digestibility, and organic matter digestibility [11]. There are also reports that EO supplementation did not affect rumen fermentation [12] but can increase the nutritional content of silage [13]. To generate a global conclusion, the differences in these results need to be further analyzed using statistical meta-analysis techniques by integrating data from each related study.…”
Section: Introductionmentioning
confidence: 99%
“…Silage enables anaerobic microbial fermentation to be dominated by lactic acid bacteria (LAB), which utilize water-soluble carbohydrates (WSC) to produce lactic acid (LA), reduce pH, and inhibit harmful microorganisms during ensilage process (Yang et al, 2020). Alfalfa (Medicago sativa L.) is a preferred perennial legume forage for livestock producers owing to its high nutritional value, especially its high crude protein (CP) concentration (Hartinger et al, 2019;Besharati et al, 2021;Netthisinghe et al, 2021). However, the second and third cuts of alfalfa in northern China are generally harvested during July and August, a period with an unreliable weather for alfalfa hay processing as it is in the rainy season.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for baled silage, since the degree of compaction of baled silage is often not as good as silo and storage silage (Broderick and Muck, 2009 ), it is easy to deteriorate and cause nutrient loss or animal poisoning (Driehuis et al, 2018 ; Penagos-Tabares et al, 2022 ). Adding fermentable carbohydrates to silage seems to be particularly effective for silage feed because they provide a source of sugar for LAB and are consumed in LA production (Besharati et al, 2021a ; Ke et al, 2023 ). Molasses contains a large amount of WSC, which can provide substrates for the growth of lactic acid bacteria to promote fermentation (Xie et al, 2021 ; Gül, 2023 ).…”
Section: Introductionmentioning
confidence: 99%